Effect of Beauveria bassiana against coffee bean borer, Hyphothenemus hampei (Ferrari) in small scale field trials - Apriyanto, Dwinardi; Nadrawati,; Bustamam, Hendri; Zarkani, Agustin (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
Coffee Berry Borer (CBB), Hyphotenemus hampei (Ferrari), is well known as scolitin beetle and a worldwide most important pest of coffee. This beetle has caught attention to entomologists worldwide to intensively study and search for the best strategy for controlling this insect. Beauveria bassiana is the most widely implemented biological control agent for CBB population, and has been mass-produced commercially in many countries. We studied the use of two local isolates of B. bassiana, Cf-Bb (isolated from naturally infected sweet potato weevil, Cylas formicarius) and Hh-Bb (isolated from naturally infected H. hampei). Small scale field efficacy study with 1 x 109 ml-1 spore concentration was conducted in a complete randomized block design, with four and one plants as the experimental units, replicated 5 and 10 times, for the first and second trial, respectively. Attacked berries and infected CBB were observed from young and mature berry clusters. The results revealed that means numbers and percentages of mature and young damaged berries varied from medium to high. Means numbers and percentages of attacked mature berries were lower in Hh-Bb than those in Cf-Bb treated and control plants. The attacked berries of younger fruits were significantly lower in plants treated with Hh-Bb and Cf-Bb isolates than those on control plants. Mean of death CBBs from B. bassiana infection was higher on attacked berries of treated plants than on those of controls. Both isolate reduced berry damage but the effects are weak. The highest reduction in the percentage of attacked berry was 33.93% and 76.47% for mature berry and young berries, in the first trial and 69.03% of mature berries in the second trial, respectively. The highest CBB mortality was 48.33%. The application of B. bassiana isolates potentially to reduce the infestation of the CBB attacked on coffee berry.